The Challenges of DNA Extraction in Different Assorted Food Matrices: A Review. Issue 10 (5th September 2018) - Sajali, Nurhayatie; Wong, Sie Chuong; Hanapi, Ummi Kalthum; Abu Bakar @ Jamaluddin, Suhaili; Tasrip, Nor Asmara; Mohd Desa, Mohd Nasir
Abstract: High‐quality DNA extracts are imperative for downstream applications in molecular identification. Most processed food products undergo heat treatments causing DNA degradation, which hampers application of DNA‐based techniques for food authentication. Moreover, the presence of inhibitors in processed food products is also problematic, as inhibitors can impede the process of obtaining high qualities and quantities of DNA. Various approaches in DNA extraction and factors in structure and texture of various food matrices affecting DNA extraction are explained in this review.